2022
DOI: 10.1111/jvim.16353
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with short‐term mortality and recurrence of status epilepticus in dogs

Abstract: Background Status epilepticus (SE) is an emergency associated with serious consequences for both patient and owner. Data regarding risk factors for short‐term mortality or recurrence in dogs with SE is limited. Objective Identify risk factors associated with short‐term mortality (euthanasia or spontaneous death) and recurrence of SE in dogs. Animals One hundred twenty‐four client‐owned dogs that sustained an episode of SE. Methods Retrospective multicenter study using data collected from medical records of dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…18,41,62 This could hopefully help in preventing the occurrence of severe ES manifestation such as CS and SE, which are associated with increased mortality and development of pharmacoresistance. 47,48,[63][64][65][66][67] Echoing what is described in human medicine, these cases raise concerns over possible therapeutic complications when switching PB brand in chronically treated dogs with IE. Therefore, careful considerations should be made when modulating antiseizure treatment in dogs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…18,41,62 This could hopefully help in preventing the occurrence of severe ES manifestation such as CS and SE, which are associated with increased mortality and development of pharmacoresistance. 47,48,[63][64][65][66][67] Echoing what is described in human medicine, these cases raise concerns over possible therapeutic complications when switching PB brand in chronically treated dogs with IE. Therefore, careful considerations should be made when modulating antiseizure treatment in dogs.…”
Section: Discussionmentioning
confidence: 96%
“…Veterinary surgeons should be proactive in measuring SPBc before PB‐brand switching and after 14–20 days after the switching is implemented 18,41,62 . This could hopefully help in preventing the occurrence of severe ES manifestation such as CS and SE, which are associated with increased mortality and development of pharmaco‐resistance 47,48,63–67 …”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with other studies that reported a metabolic-toxic disease as the main cause of SE in the emergency settings ( 3 , 37 ). However, other literature sources seem to contest this information, reporting 40.3–59% of dogs affected by IE displaying episodes of SE ( 2 , 38 ). Furthermore, it must be noted that in our retrospective study both CS and SE were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial causes of seizures are further broken down into functional (eg, idiopathic) and structural. Data from one recent study on SE documented the most common underlying aetiology to be idiopathic epilepsy (40.3 per cent), followed by structural (37.1 per cent) and reactive (22.6 per cent) (Fentem and others 2022). Table 1 outlines a list of common intra‐ and extracranial causes of seizures.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The mortality for SE in dogs can reach up to 29.8 per cent (Fentem and others 2022). In a recent study, for a population of dogs presenting to a referral hospital for seizures, SE was the cause in 16.5 per cent of cases, and for more than half of them (58 per cent), this was the dogs' first seizure event (Charalambous and others 2021).…”
mentioning
confidence: 99%